SELECTION OF WATER PERMEABLE CONCRETE COMPOSITION - Kaliknazarova Amangul Rustem qızı; Tugelbaeva Meruert Majit qızı; Tleumuratova Gulbahar kojabayevna; Amaniyazova Farida Bayrambay qızı (Journal of new century innovations, 2023)
Choosing the composition of concrete involves finding the optimal amounts of cement, water, small and large fillers, ensuring the rheological and technical properties of concrete, its brand. The standard characteristics of the components are used when choosing the concrete composition.